Divestitures creating value through strategy, structure, and implementation - Feldman, Emilie R. (McGraw Hill-Ascent Audio, 2022)
You've focused on mergers and acquisitions, but how much do you know about divestitures? Wharton professor Emilie R. Feldman provides a comprehensive primer on what strategic objectives divestitures can achieve, which businesses divestitures typically involve, what divestiture structures companies can choose from, and how to implement divestitures to maximize their financial benefits. Divestitures are among the hottest transactional structures today. Divestitures: Creating Value Through Strategy, Structure, and Implementation shows executives, board members, transactional advisors, educators, and others how strategic divestitures can be used to enhance corporate value and performance. The book is organized into three sections: Strategy: Remove problems, improve focus, reconfigure the corporate portfolio, and address regulatory requirements; Structure: Sales, spinoffs, equity carveouts, Reverse Morris Trusts, joint ventures, and tracking stocks; and Implementation: Separate the divested business, reconfigure internal processes, and reshape external perceptions. This essential book fills major gaps in the professional and academic markets, providing the only available rigorous, research-based treatment of this important strategic tool.
Online resource; title from title details screen (O'Reilly, viewed December 13, 2022)
Keywords: Business planning; Organizational effectiveness; Efficacité organisationnelle; Audiobooks; Livres audio